The excavations of Beth Shemesh, November-December 1912 - Mackenzie, Duncan, 1861-1934., author.
1 online resource (246 pages)
Keywords: "This volume presents Mackenzie's detailed discussion of his last excavations at Beth Shemesh in the light of these more recent discoveries. Although written over a century ago, Mackenzie's manuscript deserves to be better known today; it not only provides significant new information on this important site but also constitutes an intriguing historical document, shedding light on the history of field archaeology and of biblical archaeology. Moreover, Mackenzie's pioneering approach to archaeological fieldwork and the significance of his finds can often be better appreciated today, from the perspective of more recent developments and discoveries"--